2011
DOI: 10.1242/jcs.076869
|View full text |Cite|
|
Sign up to set email alerts
|

Differential endocytosis and signaling dynamics of insulin receptor variants IR-A and IR-B

Abstract: Insulin signaling comprises a complex cascade of events, playing a key role in the regulation of glucose metabolism and cellular growth. Impaired response to insulin is the hallmark of diabetes, whereas upregulated insulin activity occurs in many cancers. Two splice variants of the insulin receptor (IR) exist in mammals: IR-A, lacking exon 11, and full-length IR-B. Although considerable biochemical data exist on insulin binding and downstream signaling, little is known about the dynamics of the IR itself. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 61 publications
3
26
0
Order By: Relevance
“…S1D and E in the supplemental material), consistent with our previous observations in RBM4-depleted HEK293 cells (18). Moreover, we observed that Rbm4 knockout MEFs and adult muscles had higher levels of exon 11-skipped insulin receptor (IR), i.e., the insulin-insensitive IR-A isoform encoded by IR (19), and exon 8-skipped Pax3, which encodes a dominant negative isoform of the muscle transcription factor Pax3 (20) (Fig. 1D and E).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…S1D and E in the supplemental material), consistent with our previous observations in RBM4-depleted HEK293 cells (18). Moreover, we observed that Rbm4 knockout MEFs and adult muscles had higher levels of exon 11-skipped insulin receptor (IR), i.e., the insulin-insensitive IR-A isoform encoded by IR (19), and exon 8-skipped Pax3, which encodes a dominant negative isoform of the muscle transcription factor Pax3 (20) (Fig. 1D and E).…”
Section: Resultssupporting
confidence: 90%
“…IR-B is the predominant isoform in differentiated pancreatic ␤ cells and shows higher sensitivity to insulin (30). IR-B-activated p38 MAPK signaling is important for both pancreatic development and insulin production from ␤ cells (19). Insulin also activates the phosphatidylinositol-3-kinase-Akt pathway to promote ␤-islet survival and function (33).…”
Section: Discussionmentioning
confidence: 99%
“…IR-B is the full length mRNA isoform with exon 11 included. It is highly expressed in liver and is reported to be the major INSR isoform involved in insulin metabolism, while IR-A which lacks exon 11 plays a role in promoting cell proliferation (4648). Here, the average exon inclusion level of INSR exon 11 was 54% in PC-3E but dropped significantly to 33% in GS689.Li (Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…In murine 32D cells, IR-A induces mitogenic and antiapoptotic signals and nuclear translocation of IRS1 , whereas IR-B induces cell differentiation but not IRS1 nuclear translocation . The endocytosis of both IR isoforms in living cells has recently been evaluated using confocal microscopy (Giudice et al 2011). This study has found a higher rate of endocytosis of IR-A compared with IR-B and has correlated these differences with preferential ERK1/2 response to insulin in cells expressing IR-A and preferential Akt response to insulin in cells expressing IR-B.…”
Section: Functional Characteristics Of Ir-a Versus Ir-bmentioning
confidence: 95%